Penfluroidol Attenuates the Imbalance of the Inflammatory Response by Repressing the Activation of the NLRP3 Inflammasome and Reduces Oxidative Stress via the Nrf2/HO-1 Signaling Pathway in LPS-Induced Macrophages - Qiulin Li; Lidong Wu; Bin Cheng; Shaoyu Tao; Wei Wang; Zhiqiang Luo; Jun Fan (Mediators of Inflammation)
Objectives. Excessive inflammatory responses and reactive oxygen species (ROS) formation play pivotal roles in the pathogenesis of sepsis. Penfluroidol (PF), an oral long-acting antipsychotic drug, has been suggested to possess diverse biological properties, including antischizophrenia, antitumour effect, and anti-inflammatory activity. The purpose of this research was to explore the anti-inflammatory and antioxidative effects of penfluroidol on lipopolysaccharide (LPS)-related macrophages. Methods. The viability of RAW264.7 and THP-1 cells was measured by Enhanced Cell Counting Kit-8 (CCK-8). The production of nitric oxide was evaluated by the Nitric Oxide Assay Kit. The generation of pro-inflammatory monocytes was detected by qRT-PCR (quantitative real-time PCR) and ELISA (enzyme-linked immunosorbent assay). Oxidative stress was assessed by measuring ROS, malondialdehyde (MDA), and superoxide dismutase (SOD) activity. The protein expression of the Nrf2/HO-1/NLRP3 inflammasome was detected by western blotting. Results. Our results indicated that no cytotoxic effect was observed when RAW264.7 and THP-1 cells were exposed to PF (0–1 μm) and/or LPS (1 μg/ml) for 24 hr. The data showed that LPS, which was repressed by PF, facilitated the generation of the pro-inflammatory molecules TNF-α and IL-6. In addition, LPS contributed to increased production of intracellular ROS compared with the control group, whereas the administration of PF effectively reduced LPS-related levels of ROS. Moreover, LPS induced the generation of MDA and suppressed the activities of SOD. However, PF treatment strongly decreased LPS-induced MDA levels and increased SOD activities in the RAW264.7 and THP-1 cells. Furthermore, our research confirmed that penfluroidol repressed the secretion of pro-inflammatory molecules by limiting the activation of the NLRP3 inflammasome and reducing oxidative effects via the Nrf2/HO-1 signaling pathway. Conclusion. Penfluroidol attenuated the imbalance of the inflammatory response by suppressing the activation of the NLRP3 inflammasome and reduced oxidative stress via the Nrf2/HO-1 signaling pathway in LPS-induced macrophages.